The new spring barley variety “Bulat" - N. A. Morozov; I. V. Samsonov; N. A. Pankratova (Зерновое хозяйство России)
In the Russian Federation, barley is one of the most important food and forage grain crops. The wide spread of barley throughout the country is caused by its high ability to adapt to various environmental factors. In the Stavropol Area, where barley is mainly used as fodder, significant areas are occupied with winter barley as more productive crop, but spring barley is also given sufficient attention. Under the sharply continental climate, spring barley is the main insurance grain-forage crop in case of winter crops death. Every year, the growing need in feed requires to develop new highly adaptable varieties that are capable to produce high and stable yields with good grain quality. According to the positive results of the State Variety Testing in 2018, the new spring barley variety “Bulat”, developed by the FSEP “Prikumskaya Experimental Breeding Station”, was included into the State List of Breeding Achievements and recommended for cultivation in the North Caucasus and Nizhne-Volga regions. The variety was obtained as a result of intraspecific hybridization with the further individual selection from the hybrid population “Medikum g-68446” and “Vikont”. Due to the ripening time the variety can be referred to the group of middle-ripening varieties. The average growing season lasts 83 days. The variety is highly tolerant to drought and resistant to some diseases. The new variety produces large kernels with 53-56 g of 1000-kernel weight. The grain contains 9.8% of protein on average. During the 2015-2017 study in the Prikumskaya Experimental Breeding Station, the variety exceeded productivity of the standard variety “Strannik” on 044 t/ha. When tested at the State Variety Plots of the North Caucasus and Nizhne-Volga regions, the productivity of the variety “Bulat” reached 5.35-7.38 t/ha. The variety is intended for grain forage purposes.